2017
DOI: 10.1056/nejmoa1613210
|View full text |Cite
|
Sign up to set email alerts
|

Completion Dissection or Observation for Sentinel-Node Metastasis in Melanoma

Abstract: BACKGROUND Sentinel-lymph-node biopsy is associated with increased melanoma-specific survival (i.e., survival until death from melanoma) among patients with node-positive intermediate-thickness melanomas (1.2 to 3.5 mm). The value of completion lymph-node dissection for patients with sentinel-node metastases is not clear. METHODS In an international trial, we randomly assigned patients with sentinel-node metastases detected by means of standard pathological assessment or a multimarker molecular assay to imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
912
6
32

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 1,145 publications
(1,012 citation statements)
references
References 20 publications
30
912
6
32
Order By: Relevance
“…As reported above, all these findings stress the importance of follow guidelines, also in thin lesions 9 . In conclusion, in melanoma, sub-optimal compliance with appropriate guidelines result in poorer outcomes and increased morbidity and mortality.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…As reported above, all these findings stress the importance of follow guidelines, also in thin lesions 9 . In conclusion, in melanoma, sub-optimal compliance with appropriate guidelines result in poorer outcomes and increased morbidity and mortality.…”
supporting
confidence: 75%
“…8 Besides, the authors found that sentinel lymph-node biopsy (SNLB) reporting was just 37% of the total sample eligible for screening, showing an important gap in the routine analysis of SNLB. Indeed, although it has been showed that an immediate complete lymphnode dissection does not increase melanoma-specific survival among patients with melanoma and sentinelnode metastases 9 , SLNB should be performed in order to provide prognostic information, optimizing clinical and instrumental follow-ups and improving regional disease control.…”
mentioning
confidence: 99%
“…21,22 It is worth noting that the 8th edition AJCC Cancer Staging Manual provides specific recommendations for documentation of the now common scenario when SLN biopsy identifies tumor-involved SLNs but CLND is not performed. 9 To distinguish patients who have had a CLND from those who have not, the ''(sn)'' suffix should be appended to the N category for those who did not undergo CLND-i.e., a patient with a single tumorinvolved SLN who does not undergo CLND is pN1a(sn).…”
Section: N Category and Stage III Stage Groupsmentioning
confidence: 99%
“…A positive SLNB is the best predictor of recurrence and survival in patients with clinically node negative cutaneous melanoma (19). Indications for performing SLNB is a balance between the likelihood of finding a positive SLN, the risk of the procedure, as well as the likely benefits that will accrue to the patient from the knowledge of their SLN status (14).…”
Section: Benefitmentioning
confidence: 99%